Interaction of cyanine dyes with nucleic acids. 4. Efficient 5-fluorescent labelling of oligonucleotides with monomethyne pyrylium cyanine dye, Cyan 39 - Yarmoluk, S.M.; Kostenko, A.M.; Kornushyna, O.S.; Dubey, I.Y. (Биополимеры и клетка, 1998)
A new system for fluorescent 5'-end labelling of oligonucleotides with cyanine dyes is proposed. Reaction of primary amine with pyrylium salt was used for the efficient conjugation of monomethyne pyrylium cyanine dye with 5'-aminoalkyl oligonucleotide with simultaneous conversion of the «brightless» pyrylium dye Cyan 39 into «bright» pyridinium one Cyan 40. Запропоновано новий підхід для флюоресцентного мічення олігонуклеотидів монометиновими пірилієвими барвниками. Реакція пірилісвих солей з первинними амінами була використана для кон'югації ціанінових барвників з 5'-алкіламіно-олігонуклеотидами і перетворення нефлюоресцентного пірилієвого барвника у флюоресцентний піридинісвий – Cyan 40. Предложен новый подход для флюоресцентного мечения олигонуклсотидов монометиновыми пирилиевыми красителями. Реакция пирилиевых солей с первичными аминами была использована для конъюгации цианиновых красителей с 5'-алкилами-ноолигонуклеотидами и превращения нефлюоресцентного пирилиевого красителя во флюоресцентный пиридиниевый – Cyan 40.